Drivers of collective action and role of conflict in Kenyan fisheries co-management. (May 2021) - Murunga, Michael; Partelow, Stefan; Breckwoldt, Annette
Highlights: The sequence of early events – past experiences including conflict undermine collective action in fisheries co-management. Inter-BMU conflict linked to contradictory resource user needs and fisheries governance. Unregulated fisheries and degrading ecological conditions are associated with conflict in co-management institutions. Gear technology, market dynamics, and migrant fishers influence the severity of between-groups and within-group conflicts. Abstract: Fisheries in Kenya are experiencing social-ecological changes, impacting how they are governed via co-management. At the local level, these changes influence collective action, by influencing ecosystems, livelihoods and social cohesion. A critical research gap is to understand how fisheries conflict influences outcomes of collective action and the broader development of fisheries. In this article, we present a novel inquiry that contributes to this gap by examining the interplay between conflict and collective action within the frame of social-ecological systems research. We apply qualitative research methods, integrating Bennett's conflict typology into Ostrom's social-ecological systems framework, to present new evidence linking within and between group conflicts, to outcomes of collective action. We find leadership, gear technology, market dynamics, trust, cultural dependencies and past experiences influential in explaining dissimilar fisheries co-management outcomes in three cases. A closer look at fisheries co-management reveals that a sequence of early events, including conflict, has undermined collective action and sustainable resource use within fisheries, by altering social licence to operate and increasing transaction costs for decision making and cooperation. We use this empirical evidence to consider potential actions (e.g., recognising issue interdependencies and history) that can improve fisheries co-management in Kenya and thereby contribute to broader societal transformation.